Ecological RationalityIntelligence in the World 2012
DOI: 10.1093/acprof:oso/9780195315448.003.0116
|View full text |Cite
|
Sign up to set email alerts
|

How Estimation Can Benefit From an Imbalanced World

Abstract: This chapter analyzes how valuable the assumption of systematic environment imbalance is for performing roughand-ready intuitive estimates, which people regularly do when inferring the quantitative value of an object (e.g., its frequency, size, value, or quality). The chapter outlines how systematic environment imbalance can be quantified using the framework of power laws. It investigates to what extent power-law characteristics and other statistical properties of real-world environments can be allies of two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous research for other tasks, such as paired comparison (Czerlinski, Gigerenzer, & Goldstein, 1999; Martignon & Hoffrage, 2002) or estimation (Hertwig, Hoffrage, & Sparr, 2012; Woike, Hoffrage, & Hertwig, 2012), has shown that simple heuristics, when making inferences out of sample, can outperform models that are optimal when it comes to making inferences within the same sample for which the strategies fitted their parameters. We found the same pattern in our simulations: When making classifications out of sample with multiple cues, the two heuristic approaches, naïve Bayes and some of the fast-and-frugal trees, outperformed the model that was normative for the case of fitting known data, namely classification based on natural frequencies (or, equivalently, profile memorization).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research for other tasks, such as paired comparison (Czerlinski, Gigerenzer, & Goldstein, 1999; Martignon & Hoffrage, 2002) or estimation (Hertwig, Hoffrage, & Sparr, 2012; Woike, Hoffrage, & Hertwig, 2012), has shown that simple heuristics, when making inferences out of sample, can outperform models that are optimal when it comes to making inferences within the same sample for which the strategies fitted their parameters. We found the same pattern in our simulations: When making classifications out of sample with multiple cues, the two heuristic approaches, naïve Bayes and some of the fast-and-frugal trees, outperformed the model that was normative for the case of fitting known data, namely classification based on natural frequencies (or, equivalently, profile memorization).…”
Section: Discussionmentioning
confidence: 99%
“…People basing their choices on the choices already made by others (e.g., using imitation or copying heuristics) result in "rich-get-richer" dynamics that create distributions of popularity o f choices with just a few winners and many also-rans. Such emergent "J-shaped" distribu tions, seen in domains from music and book sales to social popularity to website visits, can in turn pre dictably influence the decisions o f others (Salganik, Dodds, & Watts, 2006;Hertwig, Hoffrage, & Sparr, 2012). Similarly, drivers seeking a parking space using a particular search heuristic, as mentioned previously, create a pattern o f available spots that is the environ ment for future drivers, who will search with their own heuristics that may fit that newly created envi ronment structure less well (Hutchinson, Fanselow, & Todd, 2012).…”
Section: Types O F Environm Ent Structurementioning
confidence: 99%
“…Table presents details of the data sets' statistical structure. Multiplicative relationships between cues and criterion often lead to highly skewed criteria distributions (often called “J‐shaped”) and linear rules do not work well in such environments (Hertwig, Hoffrage, & Sparr, ; von Helversen & Rieskamp, ).…”
Section: Simulation Study Ii: Performance Of Strategy Selection Versumentioning
confidence: 99%